2021
DOI: 10.1186/s12199-021-00969-7
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood traffic-related air pollution and risk of allergic rhinitis at 2–4 years of age modification by family stress and male gender: a case-control study in Shenyang, China

Abstract: Background Few studies have explored the modifications by family stress and male gender in the relationship between early exposure to traffic-related air pollution (TRAP) and allergic rhinitis (AR) risk in preschool children. Methods We conducted a case-control study of 388 children aged 2–4 years in Shenyang, China. These children AR were diagnosed by clinicians. By using measured concentrations from monitoring stations, we estimated the exposures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…After a mean 17-year follow-up of 1286 children based on the Toronto Child Health Assessment Questionnaire (T-CHEQ) study, Teresa To et al [ 29 ] found that early life exposure to ozone and nitrogen dioxide contributed to the development of asthma and eczema but no significant association with developing AR. Shuai Hao et al [ 30 ] used the average daily concentration of pollutants from 2 years old to the day of AR diagnosis as the early childhood exposure level and considered the effect of floor level of residence, distance between home and kindergarten on exposure estimates. This case-control study found that preschool children exposed to PM 10 and NO 2 had an increased risk of AR by 70% and 85% respectively with family stress and male gender may increase the susceptibility to AR.…”
Section: Discussionmentioning
confidence: 99%
“…After a mean 17-year follow-up of 1286 children based on the Toronto Child Health Assessment Questionnaire (T-CHEQ) study, Teresa To et al [ 29 ] found that early life exposure to ozone and nitrogen dioxide contributed to the development of asthma and eczema but no significant association with developing AR. Shuai Hao et al [ 30 ] used the average daily concentration of pollutants from 2 years old to the day of AR diagnosis as the early childhood exposure level and considered the effect of floor level of residence, distance between home and kindergarten on exposure estimates. This case-control study found that preschool children exposed to PM 10 and NO 2 had an increased risk of AR by 70% and 85% respectively with family stress and male gender may increase the susceptibility to AR.…”
Section: Discussionmentioning
confidence: 99%
“…These pollutants can modify pollen content, morphology, production, immunomodulatory properties, and immunogenicity of allergenic proteins. Consequently, they influence the severity of symptoms, particularly in sensitized individuals (40,(45)(46)(47)(48)(49)(50)(51)(52). For instance, PM 10 and PM 2.5 have been implicated in enhancing the release of Humulus pollen protein, while O 3 has shown potential to exacerbate its allergenicity, particularly in regions such as China (52).…”
Section: Pollution Pollen Production and Atmospheric Co 2 Levelsmentioning
confidence: 99%
“…Living in close proximity to traffic roads intensified the adverse effects of household environmental factors while diminishing the protective effect of domestic dogs against childhood rhinitis ( 42 44 ). Additionally, family stress and male gender were identified as potential risk factors for allergic rhinitis in preschool children, particularly in the presence of early exposure to PM 10 and NO 2 ( 45 ).…”
Section: Prenatal and First-year Exposures And Ar Diagnosismentioning
confidence: 99%

Air pollution and rhinitis

Rosario,
Urrutia-Pereira,
Murrieta-Aguttes
et al. 2024
Front. Allergy
“…who reported that PM 2.5 exposure may be correlated with childhood AR. Hao et al 951 . studied children aged 2–4 years and found that those with family stress and boys compared to girls were particularly vulnerable to increased risk of AR with early exposure to traffic‐related air pollution (Table VIII.B.3).…”
Section: Risk Factors and Protective Factors For Allergic Rhinitismentioning
confidence: 99%